2020
DOI: 10.1183/23120541.00284-2020
|View full text |Cite
|
Sign up to set email alerts
|

Design and rationale of two phase 3 randomised controlled trials (COUGH-1 and COUGH-2) of gefapixant, a P2X3 receptor antagonist, in refractory or unexplained chronic cough

Abstract: BackgroundWe present study designs, dose selection and preliminary patient characteristics from two phase 3 clinical trials of gefapixant, a P2X3 receptor antagonist, in refractory chronic cough (RCC) or unexplained chronic cough (UCC).MethodsCOUGH-1 (NCT03449134) and COUGH-2 (NCT03449147) are randomised, placebo-controlled, double-blind, parallel-group trials in subjects with RCC or UCC (age ≥18 years; cough duration ≥1 year; Cough Severity Visual Analogue Scale score ≥40 mm). The primary efficacy study perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 26 publications
1
38
1
Order By: Relevance
“…In a national-wide multi-center study, except for a eastern region (Shanghai), chronic cough patients presented an approximately equal gender distribution in western, southern, northern, and northeastern regions of China (Lai et al, 2013;Lai and Long, 2020). What's more, a female predominance among patients with refractory or unexplained chronic cough has been reported (Ryan et al, 2012;Muccino et al, 2020;Smith et al, 2020) (more specific details about sex distribution are shown in Table 1).…”
Section: Introductionmentioning
confidence: 98%
“…In a national-wide multi-center study, except for a eastern region (Shanghai), chronic cough patients presented an approximately equal gender distribution in western, southern, northern, and northeastern regions of China (Lai et al, 2013;Lai and Long, 2020). What's more, a female predominance among patients with refractory or unexplained chronic cough has been reported (Ryan et al, 2012;Muccino et al, 2020;Smith et al, 2020) (more specific details about sex distribution are shown in Table 1).…”
Section: Introductionmentioning
confidence: 98%
“…The loss of taste response seems to be due to its unselective block of P2X3 and P2X2/3Rs. Although these side effects, the medical need for patients suffering of this pathology, encouraged Merck to continue the development of gefapixant, which has recently completed two Phase III clinical trials (called COUGH-1 and COUGH-2; NCT03449134, 2020; NCT03449147, 2020) for refractory or unexplained chronic cough (Muccino et al, 2020). In these studies, gefapixant at the dose of 45 mg twice daily induced a significant reduction in 24-h cough frequency with mild to moderate alteration of taste sensitivity (Merck News release, 2020).…”
Section: Antagonistsmentioning
confidence: 99%
“…In light of published and ongoing promising data with at least four clinical programs involving P2X3 receptor-antagonists in treating chronic refractory cough (90)(91)(92)(93)(94)(95)(96)(97)(98), and with extracellular ATP and its receptors having been shown to modulate tumor development, invasion progression, and tumor microenvironment, P2X receptor antagonists may be expected also to exert an antitussive effect in lung cancerrelated cough. Further studies in this area are eagerly awaited.…”
Section: Cancer-related Coughmentioning
confidence: 99%
“…Furthermore, gefapixant showed a significant reduction in cough frequency, as assessed by randomized, double-blind, placebo-controlled Phase 2 trials ( 92 , 93 ). Recently, two Phase 3 randomized controlled trials (COUGH-1 and COUGH-2) of gefapixant in refractory chronic cough and unexplained chronic cough, evaluating more than 2000 patients, have been completed ( 94 ). Compared to placebo, treatment with 45 mg gefapixant demonstrated a significant reduction in 24-h cough frequency in patients ( 95 ).…”
Section: Cancer-related Coughmentioning
confidence: 99%